Calcified pseudotumoural mediastinal amyloidosis. Issue 9 (September 1991) - Jenkins, M C F; Potter, M
Abstract : A patient with a plasma cell neoplasm presented with progressive major air-ways obstruction from a large mediastinal calcified amyloid tumour.